ANALYSIS OF WORKING POSTURE, MSDs COMPLAINTS AND PHYSICAL ENVIRONMENTAL FACTORS IN RELATION TO LABOR PRODUCTIVITY IN PACKAGING AREA OF PT.X - Hyldajune Rizky Anjani, Dynar
This study was conducted to examine the influence of dominant factors on musculoskeletal complaints and labor productivity in food and beverage industry in Bogor District, Indonesia (PT.X). A total of 72 packaging workers were used as study participant. CMDQ Questionnaire was used to analyze musculoskeletal complaints, while work posture was evaluated using RULA. Direct measurement and observation in reference to SNI were carried out to determine work environment and workload values. Based on Permenaker No.5/2018, 100% respondents have a working climate that have meets the requirement, however merely 42% respoendents who have work station with sufficient lighting intensity. Based on Kepmenkes No. 1405/MENKES/SK/XI/2002, 100% respondents work in an area where relative humidity had met health requirement. The highest score of musculoskeletal complaints was found in low back. Work postures in most of activities were in medium risk level and all study participants were exposed to the moderate level of physical working load. The highest labor productivity lies in packing line 3, while the lowest one was found on the packing line 4. Work posture is the dominant factor causing musculoskeletal complaints, while the dominant factors affecting labor productivity is musculoskeletal complaints.